Hydrogen storage in liquid hydrogen carriers: recent activities and new trends. (1st January 2023) - Ulucan, Tolga Han; Akhade, Sneha A; Ambalakatte, Ajith; Autrey, Tom; Cairns, Alasdair; Chen, Ping; Cho, Young Whan; Gallucci, Fausto; Gao, Wenbo; Grinderslev, Jakob B; Grubel, Katarzyna; Jensen, Torben R; et al.
Abstract: Efficient storage of hydrogen is one of the biggest challenges towards a potential hydrogen economy. Hydrogen storage in liquid carriers is an attractive alternative to compression or liquefaction at low temperatures. Liquid carriers can be stored cost-effectively and transportation and distribution can be integrated into existing infrastructures. The development of efficient liquid carriers is part of the work of the International Energy Agency Task 40: Hydrogen-Based Energy Storage. Here, we report the state-of-the-art for ammonia and closed CO2 -cycle methanol-based storage options as well for liquid organic hydrogen carriers.